Health status, practices and reported effects of the MT Solar I oil spill on residents and clean up workers in Nueva Valencia, Guimaras - Malecosio, Serafin O. Jr (Danyag : Journal of Humanities and Social Sciences, 2009)
This is a cross-sectional study design that compared the self-reported health symptoms among the affected residents living along the coastal barangays affected by M/T Solar 1 oil spill in Nueva Valencia, Guimaras before and after the oil spill. It compared the symptoms between clean up and non-clean up workers of the exposed study population, and described the health status of clean up workers. There were 3,174 individuals interviewed: 2,841 belong to the exposed and 333 to the unexposed group. Of these, 124 oil spill cleanup workers in the exposed group and 37 in the unexposed were selected. The respiratory function, kidney and liver organ functions, hemoglobin and hematocrit levels of these selected clean up workers were analyzed.